Cultivation of cucurbits on bower system: an innovative way of enhancing farmers’ income - Singh, Gurdeep; Singh, Pritpal; Verma, Arti; Sodhi, Gurjinderpal Singh (Indian Farming, 2022)
The potential of cucurbits cultivation on bower system to realise the goal of doubling farmers’ income has been demonstrated. This innovative method enhanced the vegetable production, thereby increasing the land-use efficiency in south-western Punjab. In traditional systems, farmers found it difficult to manage weed infestation in fields due to the excessive growth. Cultivation of cucurbits on beds had limited success due to crop failure owing to heavy rains in monsoon. While on a bower system, vines can be easily managed. In addition, weed infestation is greatly reduced and fruit set is more because of increased sunlight penetration, thus benefitting the farmers economically.